Wireless Sensor Transmission System Using Circular Polarized Antenna At 2.4 Ghz Frequency - Hariyono Rakhmad; Agus Purwadi; Victor Phoa (Jurnal Syntax Transformation, 2023)
Sensors in the electronic world are parts that are used to detect changes in the physical or chemical environment. The output from the sensor is converted into an electrical quantity that represents the change in the environment. Sensors are widely used in agriculture, especially to detect changes in the physical or chemical environment related to plant growth, for example: temperature sensors, light sensors, soil moisture sensors, and so on. In agricultural applications that have a large area, the problem of location and distance from the sensor to the control center is a problem in itself. To solve this problem, a sensor system is designed that does not use wired (wireless) connections. In the application of wireless communication systems there is an antenna part which is very important which can affect the rate of sending sensor data. To improve the performance of wireless sensors in sending data, it is necessary to integrate the appropriate antenna with the sensor transceiver system. So this research was conducted to integrate circular polarized antennas with sensors to increase the gain in the transmission. From this integration, measurements are then taken to obtain the value of the radiation pattern, gain and bandwidth. From the resulting measurements, it can be seen that there is an increase in the gain of the wireless sensor transmission using the 2.4 GHz frequency